Larval morphology of the Madagascan endemic diving beetle genus Hovahydrus Biström, 1982 (Coleoptera: Dytiscidae) and phylogenetic comparison with other known Hyphydrini - Alarie, Yves; Michat, Mariano C.; Ranarilalatiana, Tolotra; Bergsten, Johannes (Zootaxa, 2022)
We describe for the first time the instar III larva of the diving beetle genus Hovahydrus Biström, 1982, based on H. praetextus (Guignot, 1951) and a new species yet to be described (identified here as Hovahydrus sp. near H. minutissimus (Régimbart, 1903)). We include detailed morphometric and chaetotaxic analyses of the cephalic capsule, head appendages, legs, last abdominal segment and urogomphi in order to discover useful characters for distinguishing Hovahydrus larvae from those of other known Hyphydrini (Coleoptera: Dytiscidae, Hydroporinae). A provisional parsimony analysis based on larval characteristics of 11 Hyphydrini species in eight genera was conducted using the program TNT. Larval morphology supports a close relationship between Hovahydrus, Hyphydrus Illiger, 1802, and the endemic South Africa genera Andex Sharp, 1882, Coelhydrus Sharp, 1882, Darwinhydrus Sharp, 1882 and Primospes Sharp, 1882.